Transformation of Investment Model Implementation in Tourism Industrialization Based on Local Wisdom in Badung Regency - Lis Julianti; Anak Agung Putu Wiwik Sugiantari; Ni Putu Noni Suharyanti; I Wayan Wahyu Wira Udytama (Universitas Pendidikan Ganesha, 2023)
Tourism undergoes a cycle of change that affects the culture-based Balinese tourism model by strengthening local wisdom. Tourism can run optimally if it has guarantees and cultural resilience. In addition to functioning as a tourist attraction, tourism is considered a medium to reap large profits, so tourism activities often shift cultural values and change people's lifestyles. For this reason, to control the influence of globalization on industrialization investment in tourism which has begun to follow the changes in the civilization of the industrial revolution 4.0, Badung Regency has become the rule model for the transformation of the implementation of culture-based tourism investment. This research study is descriptive-analytical, a type of research that does not stop at mere descriptions but also comes to an effort to study the characteristics of solving cases of tourism investment problems using qualitative research methods. The results of this study indicate that the people of Badung Regency's understanding of the importance of local wisdom in applying a culture-based investment model is very high. So investment activities in the tourism sector emphasize aspects of the national economy and preserve local wisdom. In addition, applying a culture-based investment model with strengthening local wisdom requires good synergy between the Government, Indigenous Village communities, tourism businesses, and investors to truly develop the concept of sustainable cultural tourism in Bali.